Liability Principles of PT. Perusahaan Listrik Negara (Persero) To the Loss of Consumers Electric Services - Riono, Riono (NORMA, 2020)
Electricity is essential for our daily needs and community and businesses because it can run their products. Recently the community and we depend on electricity, so the usage of electricity is getting an increase. All our hardware and software tools use electricity because electricity changes our style in daily life. So, the management of electricity which the State gives to PT. Perusahaan Listrik Negara (PLN) is a "State-Owned Enterprise" as we were known (BUMN). The electricity distributed to the consumers are still frequently blackout, therefore people and community fell loss with the outage, and make lawsuits to PT. PLN (Persero). This study uses a normative juridical approach, which analyzes data Referring to norms in the applicable law and regulations. The benefit of this research to contribute to the development of legal science, specifically the rule regarding consumer protection for electricity users. This research suggested that PT. PLN (Persero) commits to make a quick response when there is a blackout and give good service to the users. The consumers have to get a copy of the Power Purchase Agreement at the beginning of the installation. It is essential for the consumers as evidence to do a lawsuit when PT. PLN did not keep the promise of the Agreement.Keywords: Electricity, Blackout, Lawsuits.